Salty snacks : make your own chips, crisps, crackers, pretzels, dips, and other savory bites - Nims, Cynthia C. (Ten Speed Press, 2012)
"This collection of more than 75 recipes for savory chips, crisps, crackers, pretzels, breads, nuts, and more puts a fresh, crunchy spin on homemade snacks"--